THE WORKING CAPITAL CONCEPT–A RESTATEMENT. - Mauriello, Joseph A. (The Accounting Review, 1962)
The American Institute of Certified Public Accountants, in Chapter 7 of Bulletin 43, has issued what is to date the definitive statement on working capital. This statement has been endorsed by the American Accounting Association. This article looks afresh at the problem of determining working capital, and proposes a simple yet comprehensive restatement of principles with respect to current assets and current liabilities. The working capital section of the balance sheet is the measure of liquidity of a concern. Working capital is important to management as a measure of the fluidity of capital and as an indicator of balance in the asset and liability structure of the company. Banks and other short-term creditors are vitally interested in the amount of working capital from the standpoint of evaluating the prospect of repayment of their claims against the company. The foregoing restatement of current assets and current liabilities simplifies and reduces to the barest essentials the criteria for admitting items under working capital. Use of the principles set forth will result in a meaningful working capital amount, the asset and liability components of which are developed on a consistent and comparable basis. The inclusion under current assets of fixed assets realizable through consumption in the next fiscal period may occasion problems in estimating and measurement. The theory stated, however, is sound. In balance sheet presentation, such fixed asset portion would appear below a sub-total for the other current asset items listed.